Postoperative infusion of a low dose of dexmedetomidine reduces intravenous consumption of sufentanil in patient-controlled analgesia - Kweon, Dae-eun (Korean J Anesthesiol, 2018)
BACKGROUND: Combining adjunctive medications with patient-controlled analgesia (PCA) has been used to minimize opioid related side-effects. The aim of this study was to evaluate whether postoperative infusion of a sub-sedative dose of dexmedetomidine can reduce opioid consumption and opioid related side-effects. METHODS: We selected 60 patients from 18 to 60 years old with an American Society of Anesthesiologists physical status of 1–2 who were scheduled for elective surgery. The types of surgery were limited to thoracoscopic wedge resection of the lung and pulmonary wedge resection under a mini-thoracotomy. Patients received PCA with sufentanil upon arrival in the recovery room, along with a separate continuous infusion of dexmedetomidine that was not mixed in the PCA but started at the same time. Patients were randomly allocated to two groups: dexmedetomidine 0.15 μg/kg/h was administered to patients in group D and normal saline was administered to patients in group C. The visual analogue scale (VAS) pain score, blood pressure, pulse rate, and respiratory rate were measured at each assessment. PCA related side-effects were evaluated. RESULTS: The VAS pain score was significantly lower in the dexmedetomidine group. Patients in the dexmedetomidine group required significantly less PCA at postoperative 1–4, 4–8, and 8–24 h time intervals. The incidence of nausea was significantly less in the dexmedetomidine group, and levels of sedation and hemodynamic variables except for blood pressure at postoperative 8 h were similar between the groups. CONCLUSIONS: In conclusion, a postoperatively administered sub-sedative dose of dexmedetomidine reduces PCA sufentanil consumption and decreases nausea.